IMPACT OF AGRICULTURAL ACTIVITIES ON THE DEVELOPMENT OF THE SUGAR BEET ROOT - Палилюлько, М. І.; Семенов, О. М.; Підлісний, В. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
An increase in beet production at the present stage is possible only with the use of intensive technologies, where the integrated protection of crops from harmful organisms is of great social and economic importance. In the system of measures aimed at increasing the production of beetroots, an important place is the protection of sugar beets from diseases. Successful control of sugar beet diseases is an important reserve for increasing the yield and sugar content of root crops and improving their technological quality. A rather dangerous disease of sugar beet is the root eater, which is widespread throughout Ukraine, especially in the zone of sufficient moisture. Conducting studies to study the effect of certain agro technical measures, as more economically affordable, on the formation of harmful microorganisms that contribute to the development of root and other root diseases during the growing season, the effect of sugar beet concentration in crop rotation. In the experiments, various types of crop rotation were studied: grain-sowing, grain-cultivating (with green manure) and fruit-bearing. The technology for growing crops is generally accepted. Pesticides were not used in the experiments, with the exception of seed dressing. Studies have established that the main causative agent of the root in the conditions of the western forest-steppe of Ukraine are various species of fungi of the genus Fusarium i Aphanomyces cochliondes. The dominance of these pathogens among pathogens causes the most severe defeat of beets in the phase of the first pair of leaflets, as well as the death of plant diseases in a later period - after the formation of planting density. Studies have shown that the lowest prevalence of sugar beet diseases was observed at a saturation level of 17% when they were grown in one place after 5 years (the average degree of development of the root was 14.7%). The development of the disease increased with a decrease in the time of returning to the previous place of cultivation in the rotation. So, on average, over a three-year period, the reduction of this period to four to two years increased the degree of root beetle damage to 15.4-19.8%. At a one-year break and re-sowing, this indicator was 24.4% and 27.2%, respectively. Based on the results obtained, it can be argued that an increase in the concentration of sugar beets in the crop rotation leads to an increase in the distribution of the root.